Telehealth model versus in-person standard care for persons with type 1 diabetes treated with multiple daily injections: an open-label randomized controlled trial - Ballesta, Sílvia; Chillarón, Juan J.; Inglada, Yolanda; Climent, Elisenda; Llauradó, Gemma; Pedro-Botet, Juan; Cots, Francesc; Camell, Helena; Flores, Juana A.; Benaiges, David (Frontiers in Endocrinology, 2023)
Objective: Increasing evidence indicates that the telehealth (TH) model is noninferior to the in-person approach regarding metabolic control in type 1 diabetes (T1D) and offers advantages such as a decrease in travel time and increased accessibility for shorter/frequent visits. The primary aim of this study was to compare the change in glycated hemoglobin (HbA1c) at 6 months in T1D care in a rural area between TH and in-person visits. Research Design and Methods: randomized controlled, open-label, parallel-arm study among adults with T1D. Participants were submitted to in-person visits at baseline and at months 3 and 6 (conventional group) or teleconsultation in months 1 to 4 plus 2 in-person visits (baseline and 6 months) (TH group). Mixed effects models estimated differences in HbA1c changes. Results: Fifty-five participants were included (29 conventional / 26 TH). No significant differences in HbA1c between groups were found. Significant improvement in time in range (5.40, 95% confidence interval (CI): 0.43-10.38; p < 0.05) and in time above range (-6.34, 95% CI: -12.13-10.55; p < 0.05) in the TH group and an improvement in the Diabetes Quality of Life questionnaire (EsDQoL) score (-7.65, 95% CI: -14.67 - -0.63; p < 0.05) were observed. In TH, the costs for the participants were lower. Conclusions: The TH model is comparable to in-person visits regarding HbA1c levels at the 6-month follow-up, with significant improvement in some glucose metrics and health-related quality of life. Further studies are necessary to evaluate a more efficient timing of the TH visits.